La paz entre las naciones rivales - Barahona Plaza, Ángel Jorge (2017)
In the texts of René Girard there is an undeniable mistrust of democracy. Girard notes that democracy is the regime that favours the violent side od mimesis, that is, internal mediation. In Jean-Jacques Rousseau's texts, both the highly relevant analysis of self-esteem or envy, wich literally makes us live under the gaze of others, and a true eulogy of democracy appear.